SECURE PASSWORD FEATURES IN 2020 - Rimša, Sandis; Zeltiņš, Aleksandrs; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
Authors completed literature analysis to actualize information about secure password in 2020 year. The paper provides description of password cracking methods to identify secure password features